Mini-conjunctival autograft combined with deep anterior lamellar keratoplasty for chronic sequelae of severe unilateral chemical burn: A case report. (November 2021) - Kate, Anahita; Basu, Sayan
Abstract: Introduction and importance: This case describes a novel technique combining a mini-conjunctival limbal autograft (CLAU) with a deep anterior lamellar keratoplasty (DALK) in a case of chemical injury sequelae. Case presentation: A 19-year-old female presented with total limbal stem cell deficiency (LSCD) and a vascularized corneal scar in the visual axis of the left eye, 4 years following a chemical injury. In order to treat the LSCD and simultaneously visually rehabilitate the patient, a mini-CLAU with DALK was carried out. Two separate one clock-hour CLAUs were harvested from the right eye and secured in the left. The graft was clear in the initial postoperative period and maintained its clarity over 15 months of follow period with a visual acuity of 20/30 with scleral contact lenses. The mini-CLAUs sustained a stable and well epithelialized corneal surface during the same period. Clinical discussion: The use of the mini-CLAUs instead of the traditional CLAU circumvents the complication of an iatrogenic LSCD in the donor eye as the size of the donor grafts is smaller (1–2 clock hours versus 6–8 clock hours). Despite the smaller size, these grafts are efficacious in maintaining a well epithelialized corneal surface even in cases of total LSCD. The autologous nature of the graft defers the need for immunosuppression and its peripheral location facilitates ease of the surgical technique when combined with a keratoplasty. Conclusion: This novel single-staged procedure is an effective technique to reestablish a stable ocular surface and to visually rehabilitate cases of chronic chemical injury with good long-term outcomes. Highlights: Severe ocular burns need both corneal and limbal transplantation. Anterior lamellar keratoplasty is preferred over penetrating grafts. Mini-conjunctival limbal grafts can be obtained safely from the healthy fellow eye. The need for long-term systemic immunosuppression is minimized in this approach. This combined technique leads to good and sustainable functional recovery.